PHILOSOPHICAL REPRESENTATION OF FEMALE ARTISTIC IMAGES IN OBJECTIVISM - A. O. Muntian (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. Based on actualization of gender discursive features, the current piece aims to clarify and accentuate the manifestation of gender-philosophical ideas interaction: feminism in the framework of objectivism. The source material for the current article is a novel by Ayn Rand "Atlas Shrugged", which is a philosophical work on objectivism. Theoretical basis. The development of the gender discourse, in particular the discourse of feminism is researched from the retrospective angle. This piece is an attempt to underline peculiarities of female artistic images representation in Rand’s work and the way Rand’s novel influenced the logical development of feminist discourse. Discourse of feminism is a rather peculiar notion for Objectivism, where the notion of gender is, theoretically, annihilated as far as gender is irrelevant for both personal and professional growth, however, practically, gender representation and actualization is ubiquitous in Rand’s philosophy. Originality. The distinctive features of gender discourse in Objectivism are highlighted in this piece; the results are based on the application of comparative analysis. It is argued that philosophy itself may well be perceived through a literary work of fiction, thus making artistic images prototypes of philosophy functionaries. Conclusion. "Atlas Shrugged" is not merely a literary fiction, but rather a philosophical treatise on Objectivism, which is a philosophy of individual struggle and achievement. The main female protagonist of "Atlas Shrugged", Dagny Taggart, is a staunch supporter of Objectivism. In Rand’s opinion Dagny Taggart is a prototype of a true woman of utopian American capitalist society, and it is her artistic image that was misinterpreted by supporters of feminist movement ideas and Dagny Taggart became an icon of feminism, whereas in reality Dagny’s discourse is rather a discourse of femininity, for Dagny despises everything that is connected with feminist ideas and practices, and, it is an error to weave her discourse into a much wider feminist discourse.